Pauline theology as a way of life: a vision of human flourishing in Christ - Jipp, Joshua W. (Baker Academic, a division of Baker Publishing Group, 2023)
"A respected New Testament scholar places Paul's writings within the timeless pursuit of human flourishing, happiness, and the good life, reframing the task of Pauline theology as an encouragement to pursue a particular way of life"--